THE ROLE OF EMOTION REGULATION IN FAMILY RESILIENCE FOR CAREGIVERS OF PATIENT WITH SCHIZOPHRENIA CONSIDERING CAREGIVING BURDEN - Ni Nyoman, Armelia Dewi; Fitryasari, Rizky; Tristiana, RR. Dian (Universitas Airlangga, 2026)
ABSTRACT Introduction: Caregivers of schizophrenia patients face emotional, physical, and social stress that can weaken family resilience. Their mental health is often at risk, causing distress and unstable emotion regulation. These factors may harm care quality, highlighting need to support caregivers’ mental health and emotion regulation. Method: A systematic review of quantitative studies was conducted. Relevant full-text articles were sourced from five databases: ProQuest, Science direct, Sage Journals, and Taylor & Francis database inception to April 2025. Articles used from 2020 to 2025. Searching for articles or journals uses keywords and Boolean operators. Bias was assessed with Joanna Briggs Institute (JBI) tool. We followed the protocols and rules of Preferred Reporting Items for Systematic Reviews (PRISMA) guidelines. Results: A total of 1.567 article were found. There were 10 relevant papers found in the literature search. Total of 2.007 participants age 18 to 85 years, from 7 countries, families caring for a family member with a diagnosis of schizophrenia. The majority of studies (n=10) reported that family resilience is influenced by several factors, including sociodemographic characteristics, educational background, stigma, economic conditions, physical health status, psychosocial factors especially particularly adaptive coping strategies and the quality of the caregiver with patient relationship. Conclusions: This review highlights that emotion regulation, particularly through adaptive strategies like cognitive reappraisal and positive coping, plays a key role in enhancing family resilience among caregivers of individuals with schizophrenia. Strengthening emotional regulation can reduce caregiver burden and improve overall psychological well-being. Keyword: emotion regulation; resilience; family caregiver; schizophrenia; burden